Secret sharing scheme based technique for authentication of documents images - Ghazi, Muna; Salman, Hana M. A. (Engineering and Technology Journal, 2014)
صورة النصوص الرقمية هي شكل من أشكال النسخ الإلكترونية للحفاظ على المعلومات الهامة. لقد أصبحت الصور الرقمية شائعة لذلك فمن السهل نسخ و تزييف مضمون صورة الوثيقة الرقمية و ادعاء ملكيتها. هذا البحث يقدم تقنية لتصديق النصوص الصورية باستخدام تقنيات المشاركة بالسرية (secret sharingschemes) حيث يمكن أن : 1. المصادقة على صحة الوثيقة. 2. يتحقق من مالك صورة الوثيقة. 3. تحديد موضع التغيير في صورة الوثيقة. 4. اكتشاف الخطأ في صورة الوثيقة، و 5. تصحيح الخطأ في صورة الوثيقة. نتيجة المقارنة مع طرق مختلفة لتصديق صحة النصوص الصورية تبين، لا يوجد تشويه بصورة العلامة المائية، الطريقة لها القابلية على تحديد موقع التزييف، القدرة على التصليح، و المصادقة على كل بلوك بحجم (3 x 2)، توزيع أجزاء النصوص الصورية المصدقة في داخل الصورة باستخدام طريقة البت الأقل أهمية. Digital document image is a form of persevering important information, and, because of rapid technological development, it is easy to copy, counterfeit this digital document image and claim ownership. Therefore this paper presents a document image authentication scheme based on using secret sharing that can : 1. Authenticate document image. 2. Verify the owner of the document image. 3. Localize the alteration in the document image. 4. Detect the error in the document image, and 5. Correct the error in the document image. According to comparison of different document image authentication methods, there is no distortion in stego image, the method has capability to locate the tampering, repair capability, reported authentication precision for each (2 X 3) block, distribution of authenticated image parts in the entire image and manipulating data embedding in LSB(least Signification Bit).